Tooth Germ Development After Autotransplantation of an Immature Permanent Tooth - Su-Hsyen Lai, Cheryl; Hui Wen Sim, Michelle; Hui Chan, Boon (Journal of dentistry for children (Chicago, Ill.), 2022)
Hypodontia is commonly associated with cleft lip and/or palate and can be managed by autotransplantation of teeth. In this case report, autotransplantation of the immature mandibular right second premolar to replace the congenitally missing maxillary right second premolar was performed successfully in an 11-year-old Chinese male. An ectopic tooth resembling a premolar tooth was subsequently noted to be developing palatal to the root apex of the transplanted tooth one month after surgery. The development of a dental tooth germ at the site of the autotransplantation post-surgery is a possibility and clinicians should be aware and monitor for such development. The development of a tooth germ post-autotransplantation of an immature tooth could provide a new perspective into tooth organogenesis in patients with agenesis of permanent teeth.